10) 9 - 2(-4x + 7) = 7
9 + 8x - 14 = 7
8x = 7 + 5
8x = 12
x = 1,5
11) 2x + 2 = - 3
2x = - 3 - 2
2x = - 5
x = - 2,5
![x+7-\frac{x}{3}=7\\\\3x+21-x=21\\\\2x=21-21\\\\ 2x=0\\\\ x=0 x+7-\frac{x}{3}=7\\\\3x+21-x=21\\\\2x=21-21\\\\ 2x=0\\\\ x=0](https://tex.z-dn.net/?f=x%2B7-%5Cfrac%7Bx%7D%7B3%7D%3D7%5C%5C%5C%5C3x%2B21-x%3D21%5C%5C%5C%5C2x%3D21-21%5C%5C%5C%5C+2x%3D0%5C%5C%5C%5C+x%3D0)
14) 4x + 7 = 0
4x = - 7
x = - 1,75
15) (- 5x + 3)(-x + 6) = 0
Произведение двух множителей тогда равно нулю, когда хотя бы один из них равен нулю, значит :
или - 5x + 3 = 0
- 5x = - 3
x = 0,6
или -x + 6 = 0
- x = - 6
x = 6
Ответ : 0,6 ; 6